New species and new records of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Chacoan Domain in northeastern Brazil - Rodrigues, Jackson A. O.; Nascimento, Stênio R. S.; Raimundi, Erikcsen A.; Lima, Lucas R. C. (Zootaxa, 2023)
The genus Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) is endemic to South American with 27 described species. In Brazil, 21 of these are known to occur. The present paper describes three new species of Miroculis Edmunds, 1963. Miroculis (Miroculis) botafora sp. nov. is described based on a male imago collected in a transition area between the Cerrado and Caatinga biomes in Piauí State, Brazil. Two species are described based on nymphs and adults: Miroculis (Miroculis) azevedoi sp. nov. and Miroculis (Miroculis) quilombola sp. nov.; both were collected in a Cerrado region of Maranhão State, Brazil. Additionally, new distribution records of Miroculis (Miroculis) fittkaui Savage & Peters, 1983 are provided.